Preterm birth impairs postnatal lung development in the neonatal rabbit model - Thomas Salaets; Margo Aertgeerts; André Gie; Janne Vignero; Derek de Winter; Yannick Regin; Julio Jimenez; Greetje Vande Velde; Karel Allegaert; Jan Deprest; Jaan Toelen (Respiratory Research, 2020)
Abstract Background Bronchopulmonary dysplasia continues to cause important respiratory morbidity throughout life, and new therapies are needed. The common denominator of all BPD cases is preterm birth, however most preclinical research in this area focusses on the effect of hyperoxia or mechanical ventilation. In this study we investigated if and how prematurity affects lung structure and function in neonatal rabbits. Methods Pups were delivered on either day 28 or day 31. For each gestational age a group of pups was harvested immediately after birth for lung morphometry and surfactant protein B and C quantification. All other pups were hand raised and harvested on day 4 for the term pups and day 7 for the preterm pups (same corrected age) for lung morphometry, lung function testing and qPCR. A subset of pups underwent microCT and dark field imaging on day 0, 2 and 4 for terms and on day 0, 3, 5 and 7 for preterms. Results Preterm pups assessed at birth depicted a more rudimentary lung structure (larger alveoli and thicker septations) and a lower expression of surfactant proteins in comparison to term pups. MicroCT and dark field imaging revealed delayed lung aeration in preterm pups, in comparison to term pups. Preterm birth led to smaller pups, with smaller lungs with a lower alveolar surface area on day 7/day 4. Furthermore, preterm birth affected lung function with increased tissue damping, tissue elastance and resistance and decreased dynamic compliance. Expression of vascular endothelial growth factor (VEGFA) was significantly decreased in preterm pups, however in the absence of structural vascular differences. Conclusions Preterm birth affects lung structure and function at birth, but also has persistent effects on the developing lung. This supports the use of a preterm animal model, such as the preterm rabbit, for preclinical research on BPD. Future research that focuses on the identification of pathways that are involved in in-utero lung development and disrupted by pre-term birth, could lead to novel therapeutic strategies for BPD.